Flexible working arrangement sebagai strategi efisiensi anggaran dalam pemerintahan - Gede Wijaya Kusuma; Salman, Agus; Prima Firmansyah, Jovan; Pramono, Wahyudi; Budi Prayitno, Rahadi; P. Simarmata, Rajanner (Cv. Kalimasada Group, 2024)
This research analyzes the implementation of Flexible Working Arrangement as a response to the Indonesian government's budget efficiency policy, particularly in relation to Presidential Instruction number 1 of 2025. Through a qualitative approach with literature study methodology, the research explores how flexibility in work location and time can drive budget efficiency without sacrificing productivity and public service quality. Analysis results indicate that Flexible Working Arrangement has the potential to reduce office operational costs, decrease the need for permanent office space, and optimize resource allocation. Studies from various countries confirm the benefits of Flexible Working Arrangement in improving employee retention and work welfare, despite challenges such as digital infrastructure investment and remote performance management. Effective implementation requires policies that support digital transformation and adaptive human resource governance. In the long term, Flexible Working Arrangement is not merely a temporary solution for budget efficiency but can become a transformative strategy in Indonesia's government work system.